The slab effect of composite frames: From modified fiber modeling to seismic fragility assessment. (November 2021) - Lin, Yongjun; Zhang, Xianzhao
Abstract: The slab spatial composite effect (SSCE) is of considerable importance in the field of engineering as it greatly influences the vertical load-bearing capacity and lateral load resistance of composite frame structures. In this study, the existing uniaxial material-constitutive models of concrete ( Concrete02 ) and steel ( Steel02 ) in the Open System for Earthquake Engineering Simulation (OpenSees) were modified based on three effective flange widths of composite beams under two critical limit states. An improved fiber model was developed to capture the SSCE of composite frames by combining the conventional fiber models and new material-constitutive models. Through three validation studies, the ability of the proposed fiber model to trace the SSCE accurately and efficiently was established based on modeling and comparison of the representative composite frames available in literature. Moreover, seismic fragility assessment was conducted for a 10-story spatial composite frame subjected to bidirectional horizontal seismic excitation based on an incremental dynamic analysis. The comprehensive numerical simulation results indicate that the conventional fiber model without constitutive model modifications leads to significant overestimation of the probability of the structure being a specified limit state under different ground motion intensities and site classes. The conventional fiber model results are at most 47.1%, 72.0%, 53.5%, and 49.6% higher than those obtained using the improved fiber model in terms of the structure being slightly, moderately, extensively, and completely damaged, respectively. This means that the potential economic advantages of composite frames can be explored by reasonably considering the SSCE. Graphical abstract: Unlabelled Image Highlights: An improved fiber model for simulating the slab spatial composite effect of composite frames Two new uniaxial material models are designed and implemented into OpenSees. Seismic fragility assessment of a high-rise composite frame